Activité Antifongique In Vitro des Extraits de Cinq Plantes Locales sur Colletotrichum Higginsianum, Fusarium Oxysporum et Rhizopus Stolonifer, Agents Pathogènes de la Papaye (Carica Papaya L.) et de la Tomate (Solanum Lycopersicum L.) - Kamelé, Kossonou Yao; Clémentine, Kouakou-Kouame Amenan; Carole, Koffi Affoué; Mesmin, Koffi Yao; Honora, Tra Bi Fézan; Kablan, Tano (European Scientific Journal, ESJ, 2019)
To evaluate the in vitro antifungal activity of plant extracts on the growth of fungal pathogens responsible for tropical fruit rot (papaya and tomato). Methanol, dichloromethane, and water distillated of Trichilia heudelotii, Nesogordonia papaverifera, Celtis mildbraedii, Cola gigantea and Triplochiton scleroxylon were tested on strains of isolated and identified fungi from fruits of papaya and tomato. Growth inhibition tests carried out made it possible to measure their level of resistance in presence of plant extracts. Tube reactions were performed for the detection of classes of phytochemicals compounds responsible for the activity of plant extracts. Antifungal tests revealed that the extracts of all plants were fungicidal at a concentration of 10 mg / mL on fungal Colletotrichum higginsianum, Fusarium oxysporum, Rhizopus stolonifer, pathogens of papaya and tomato. Fusarium oxysporum was the most sensitive strain to methanolic and dichloromethane extracts of the organs of all plants tested. Phytochemical investigations revealed the presence of phenolic compounds, sterols and polyterpenes in the extracts of plant organs studied. The presence of these compounds may explain the antifungal activity of the extracts of these plants on all the selected strains. The use of plant extracts for the development of formulation technology of biofungicides for the control of post-harvest losses of papaya and tomato due to pathogens is proving to be a good alternative to the toxic chemicals products used for the conservation of these foods. Évaluer l’activité antifongique in vitro des extraits de plantes sur la croissance des pathogènes fongiques responsables de la pourriture des fruits tropicaux (papaye et tomate). Les extraits au méthanol, dichlorométhane, et à l’eau de Trichilia heudelotii, Nesogordonia papaverifera, Celtis mildbraedii, Cola gigantea et Triplochiton scleroxylon ont été testés sur des souches de champignons isolées et identifiées des fruits de papaye et de tomate. Les tests d’inhibition réalisés ont permis de mesurer leur niveau de résistance. Des réactions en tubes ont été effectuées pour la détection des classes de composés responsables de l’activité des extraits de plantes. Les tests antifongiques ont révélé que les extraits de toutes les plantes ont été fongicides à la concentration de 10 mg/mL sur les fongiques Colletotrichum higginsianum, Fusarium oxysporum, Rhizopus stolonifer, pathogènes de la papaye et de la tomate. Fusarium oxysporum a été la plus sensible des souches aux extraits méthanoliques et dichlorométhanes des organes de toutes les plantes. Les investigations phytochimiques ont révélé la présence de composés phénoliques et stérols et polyterpènes dans les extraits des divers organes de plantes étudiées. La présence de ces composés a permis d’expliquer l’activité antifongique des extraits de ces plantes sur l’ensemble des souches sélectionnées. L’utilisation des extraits de plantes pour la formulation de biofongicide dans le contrôle des pertes post-récoltes dues aux agents pathogènes de la papaye et de la tomate s’avère être une belle alternative aux produits chimiques toxiques utilisés pour la conservation de ces produits.